A Modified Matrix Algorithm Dichotomy for Distribution Network Fault Location - Yan Hanyu; Wu Xueying; Lin Chunlan; Liu Haiyan (E3S Web of Conferences, 2020)
The operation mode of distribution network is diversified, and it is difficult to accurately locate the fault point when the fault occurs in the case of multiple power sources and branches. In order to accurately locate the fault point and quickly restore the power supply in the fault-free area, a bisection fault location method based on improved matrix is proposed. According to the feedback information of terminal feeder equipment, the improved matrix algorithm is used to form the grid structure matrix and fault information matrix base on the connection relationship of distribution network. The grid structure matrix reflects the connection relationship between nodes and the power flow direction of the distribution network in normal operation. The fault information matrix is the flow direction of power flowing through terminal equipment when the system fails. According to the grid matrix and fault information matrix, the fault judgment matrix is obtained to judge the fault area. Finally, the dichotomy method is used to judge the fault area and determine the specific fault point. The effectiveness and practicability of the method are verified by an example.